Effects of Mg and Sr co-addition on the densification and biocompatible properties of calcium pyrophosphate - Kim, Dong Wook; An, Jae Sul; Cho, In Sun (Ceramics International, 2018)
The influences of Mg and Sr co-addition on the phase transformation and densification behavior of calcium pyrophosphate (Ca2P2O7, CPP) were investigated. We found that the addition of an optimum content of Mg increases bulk density of CPP ceramic because it restrains the volume-expansion (i.e., crack formation) that occurs due to the phase transformation from beta- to alpha-CPP phase. Importantly, when Mg (1 wt%) and a small content of Sr (0.3 wt%) were added together, the highest bulk density (98.3%) was achieved. Further, the co-addition of them greatly improves biocompatibility when compared to CPP with the addition of only Mg.
Keywords: Bulk density; Ca2P2O7; Calcium pyrophosphate; Coaddition; Densification behavior; Volume expansion; Additives; Biocompatibility; Ca2P2O7; Densification behavior; Phase transformation